Question and Answers Forum

All Questions      Topic List

Others Questions

Previous in All Question      Next in All Question      

Previous in Others      Next in Others      

Question Number 396 by 123456 last updated on 25/Jan/15

(1/2)−(3/4)+(5/6)−(7/8)+∙∙∙=x  (1/2)−(1/4)+(1/6)−(1/8)+...=y  −−−−−−−−−−−−−−−−−−  Σ_(i=0) ^∞ ((2i+1)/2^i ) converge?

$$\frac{\mathrm{1}}{\mathrm{2}}−\frac{\mathrm{3}}{\mathrm{4}}+\frac{\mathrm{5}}{\mathrm{6}}−\frac{\mathrm{7}}{\mathrm{8}}+\centerdot\centerdot\centerdot={x} \\ $$$$\frac{\mathrm{1}}{\mathrm{2}}−\frac{\mathrm{1}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{6}}−\frac{\mathrm{1}}{\mathrm{8}}+...={y} \\ $$$$−−−−−−−−−−−−−−−−−− \\ $$$$\underset{{i}=\mathrm{0}} {\overset{\infty} {\sum}}\frac{\mathrm{2}{i}+\mathrm{1}}{\mathrm{2}^{{i}} }\:\mathrm{converge}? \\ $$

Commented by 123456 last updated on 28/Dec/14

x+y=1−1+1−1+1−1+1−1+∙∙∙

$${x}+{y}=\mathrm{1}−\mathrm{1}+\mathrm{1}−\mathrm{1}+\mathrm{1}−\mathrm{1}+\mathrm{1}−\mathrm{1}+\centerdot\centerdot\centerdot \\ $$

Answered by prakash jain last updated on 29/Dec/14

Σ_(i=0) ^∞ ((2i+1)/2^i )=2Σ_(i=0) ^∞  (i/2^i ) +Σ_(i=0) ^∞ (1/2^i )=2S_1 +S_2   S_1 =Σ_(i=0) ^∞  (i/2^i )=0+(1/(2 ))+(2/2^2 )+(3/2^3 )+(4/2^4 )+...  (S_1 /2)=(1/2^2 )+(2/2^3 )+(3/2^4 )+...  S_1 −(S_1 /2)=(1/2)+(1/2^2 )+(1/2^3 )+..=((1/2)/(1−(1/2)))=1⇒S_1 =2  S_2 =1+(1/2)+(1/2^2 )+...=2  2S_1 +S_2 =6

$$\underset{{i}=\mathrm{0}} {\overset{\infty} {\sum}}\frac{\mathrm{2}{i}+\mathrm{1}}{\mathrm{2}^{{i}} }=\mathrm{2}\underset{{i}=\mathrm{0}} {\overset{\infty} {\sum}}\:\frac{{i}}{\mathrm{2}^{{i}} }\:+\underset{{i}=\mathrm{0}} {\overset{\infty} {\sum}}\frac{\mathrm{1}}{\mathrm{2}^{{i}} }=\mathrm{2}{S}_{\mathrm{1}} +{S}_{\mathrm{2}} \\ $$$${S}_{\mathrm{1}} =\underset{{i}=\mathrm{0}} {\overset{\infty} {\sum}}\:\frac{{i}}{\mathrm{2}^{{i}} }=\mathrm{0}+\frac{\mathrm{1}}{\mathrm{2}\:}+\frac{\mathrm{2}}{\mathrm{2}^{\mathrm{2}} }+\frac{\mathrm{3}}{\mathrm{2}^{\mathrm{3}} }+\frac{\mathrm{4}}{\mathrm{2}^{\mathrm{4}} }+... \\ $$$$\frac{{S}_{\mathrm{1}} }{\mathrm{2}}=\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{2}} }+\frac{\mathrm{2}}{\mathrm{2}^{\mathrm{3}} }+\frac{\mathrm{3}}{\mathrm{2}^{\mathrm{4}} }+... \\ $$$${S}_{\mathrm{1}} −\frac{{S}_{\mathrm{1}} }{\mathrm{2}}=\frac{\mathrm{1}}{\mathrm{2}}+\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{2}} }+\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{3}} }+..=\frac{\frac{\mathrm{1}}{\mathrm{2}}}{\mathrm{1}−\frac{\mathrm{1}}{\mathrm{2}}}=\mathrm{1}\Rightarrow{S}_{\mathrm{1}} =\mathrm{2} \\ $$$${S}_{\mathrm{2}} =\mathrm{1}+\frac{\mathrm{1}}{\mathrm{2}}+\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{2}} }+...=\mathrm{2} \\ $$$$\mathrm{2}{S}_{\mathrm{1}} +{S}_{\mathrm{2}} =\mathrm{6} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com